P261 Tiotropium Safety And Performance In Respimat® (tiospir™): Safety And Efficacy In Patients Naïve To Treatment With Anticholinergics. (10th November 2014) - Wise, R; Calverley, P; Dahl, R; Dusser, D; Metzdorf, N; Mueller, A; Fowler, A; Anzueto, A
Abstract : Introduction: The TIOSPIR™ trial showed similar safety and exacerbation efficacy profiles for tiotropium Respimat ® and HandiHaler ® in patients with chronic obstructive pulmonary disease (COPD). We present here the results for patients who were naïve to anticholinergic treatment at baseline. Methods: TIOSPIR™ (n = 17, 135), a 2–3 year, randomised, double-blind, parallel-group, event-driven trial, compared safety and efficacy of once-daily tiotropium Respimat ® 5 and 2.5 µg with HandiHaler ® 18 µg in patients with COPD. Primary endpoints were time to death (noninferiority of Respimat ® 5 or 2.5 μg versus HandiHaler ® ) and time to first COPD exacerbation (superiority of Respimat ® 5 μg versus HandiHaler ® ). Safety, including cardiovascular safety, was assessed. Results: Overall, 6966 patients from TIOSPIR™, naïve to anticholinergic treatment at baseline, were randomised and treated (n = 2345, n = 2312 and n = 2309 for tiotropium Respimat ® 2.5 and 5 µg and HandiHaler ® 18 µg). There was similar risk of death (vital status follow up) (measured as time to death) for the Respimat ® groups versus HandiHaler ® (Respimat ® 5 µg: hazard ratio [HR], 0.93; 95% confidence interval [CI], 0.75–1.17; Respimat ® 2.5 µg: HR, 1.05; 95% CI, 0.84–1.30) with similar results for the on-treatment sensitivity analysis (Respimat ® 5 µg: HR, 0.91; 95% CI, 0.71–1.17; Respimat ® 2.5 µg: HR, 1.11; 95% CI, 0.87–1.40). Risk of exacerbation was also similar for the Respimat ® groups versus HandiHaler ® (measured as time to first exacerbation) (Respimat ® 5 µg: HR, 0.99; 95% CI, 0.90–1.08; Respimat ® 2.5 µg: HR, 1.04; 95% CI, 0.95–1.14). Risk of major adverse cardiovascular event (MACE) or fatal MACE were similar for the Respimat ® groups versus HandiHaler ® (MACE: Respimat ® 5 µg: HR, 1.20; 95% CI, 0.88–1.63; Respimat ® 2.5 µg: HR, 1.11; 95% CI, 0.81–1.51; fatal MACE: Respimat ® 5 µg: HR, 1.14; 95% CI, 0.75–1.71, Respimat ® 2.5 µg: HR, 1.12; 95% CI, 0.75–1.69). Conclusions: Analogous to the global analysis, patients naïve to anticholinergic treatment and treated with tiotropium Respimat ® 2.5 or 5 µg or HandiHaler ® in the TIOSPIR™ trial exhibited similar safety and exacerbation efficacy profiles.